RARE-08. GRADING CONSIDERATIONS FOR MENINGEAL SOLITARY FIBROUS TUMOR/HEMANGIOPERICYTOMA. (5th November 2018) - Fritchie, Karen; Jensch, Kassandra; Jenkins, Sarah; Link, Michael; D Brown, Paul; Rodriguez, Fausto; Guajardo, Andrew; Brat, Daniel; Velazquez Vega, Jose'; Perry, Arie; Wu, Ashley; Raleigh, David; et al.
Abstract: Meningeal solitary fibrous tumor (SFT)/hemangiopericytoma (HPC) is a rare tumor with propensity for recurrence and metastasis. We compared the WHO 2016 CNS tumor classification (CNS-G), a 3-tier system based on histopathologic phenotype and mitotic count, to the WHO 2013 Soft Tissue classification (ST-G), a 2-tier system based on mitotic count alone, in a cohort of 133 patients (59 female, 74 male; mean age 54 years [range 20–87]) with meningeal SFT/HPC. Tumors were pathologically confirmed through review of the first tumor resection (n=97), local recurrence (n=35) or distant metastasis (n=1). STAT6 immunostain showed nuclear expression in 132 cases. NAB2-STAT6 fusion was detected in 99 (of 111) successfully tested tumors (89%) including the lone STAT6 immunonegative tumor. Tumors were classified as grade 1 (n=43), 2(n=41) or 3 (n=49) using the CNS-G, and SFT (n=84) or malignant SFT (n=49) by using the ST-G. Necrosis was present in 16 cases (12%). On followup, 42 patients had at least 1 subsequent recurrence, including 8 with metastases. 29 patients died. On univariate analysis necrosis (p=0.0018) and CNS-G or ST-G (p-value respectively 0.014, 0.0041) were significantly associated with recurrence-free (RFS) but not overall survival (OS). NAB2-STAT6 fusion type was not associated with RFS or OS. Ten-year RFS was 61, 58 and 34% for CNS-G 1, 2 and 3 versus 59 and 34% for ST-G SFT and malignant SFT, respectively. Ten-year RFS was 0% and 56% for tumors with and without necrosis. Our data suggest that SFT/HPC are better stratified using a two-tiered grading scheme. On multivariate analysis, necrosis was an independent predictor of RFS (HR 2.9, p=0.016) while ST-G was not quite significant (HR=1.9, p=0.062), suggesting necrosis should be reintroduced among SFT/HPC grading criteria.